A potencialidade de uma história em quadrinho autoral para o ensino de Química: uma análise docente para a Educação Básica e Ensino Superior - SENA, Emilay Thamiely Tavares de (2022)
The research, result of this Course Completion Work, carried out an analysis on the didactic potential of a Comics to approach concepts of Chemical Sciences in High School and Higher Education through the perspective evaluative of teachers working at the respective levels of education mentioned above. The object of study is entitled “H-Quí: Química das transformações”. It is an authorial didactic resource produced with the objective of approaching chemical contents from the contextualization of a zombification ritual carried out in the Vodou belief, where Tetrodotoxin and Scopolamine (substances responsible for the occurrence of zombification) are the main agenda for the study of zombification narrative of H-Quí. Such substances give rise to an approach of theoretical concepts associated with chemical experimental tests, which encourages the need to identify the contents that have the greatest potential to be approached from the possible didactic application of H-Quí with students. That said, the analysis of the didactic potential and the identification of chemical contents were carried out from a research with the contribution of qualitative research that took place through the application of a questionnaire with inductive questions formulated in the light of the categories created by Testoni and Abib (2004). Subsequently, they were reorganized to obtain two new categories that represented a greater expansion of the analysis carried out in this work, namely: (i) Structural aspects of the H-Quí narrative and (ii) Identification of chemical contents. From the organization of the answers in the aforementioned axes, it was possible to observe in the first category that the contextualization of the zombie theme, the textual explanations, image representations and the organization of the contents, elements intrinsic to the H-Qui narrative, directly interfere in the good employability of this didactic resource, since such elements were evaluated by educators as being of paramount importance to enhance and facilitate students' interest in “scientific knowledge”. In turn, the identification of chemical contents, the second axis of the results, showed the possibility of working with different concepts both in EM and in ES. However, it is worth mentioning that there was an identification of predominance of concepts of Organic Chemistry in both levels of studies studied, which has evidence that H-Che has greater potential to work with such contents. Finally, a synthesis of the main results is carried out in order to observe the key points that classify the material produced as a potential resource.